Comparison of two models of the dimer–dimer reaction on composite catalyst - Katauskis, Pranas (Lietuvos matematikos rinkinys, 2017)
In this paper two mathematical models of the dimer–dimer reaction on supported catalysts are compared. The PDE model describe the bulk diffusion of both reactants and product, adsorption and desorption, the surface diffusion of adsorbates and intermediate. The ODE model is derived from the first, assuming that all materials are well-mixed. The catalytic reactivity, calculated using the PDE and ODE models, is compared for two variants of reactants adsorption and variuos bulk and surface diffusion.
Keywords: surface reaction; adsorption; desorption; spillover